Anterior chamber parameters after laser iridotomy in primary angle-closure spectrum - B. S. Chetana; Y. M. Manjula (Kerala Journal of Ophthalmology)
Aim: To evaluate anteriorchamber parameter after laser iridotomy in primary angle closure disease spectrum. Objectives: To study central anterior chamber depth morphology (CACD) anterior chamber volume (ACV), anterior chamber angle (ACA) in primary angle closure disease patients using rotating scheimpflug camera (pentacam) before and after laser PI. Methods: 91 eyes of 50 patients having PACD changes in CACD, ACV, ACA were evaluated using rotating scheimpflug camera before and after laser peripheral iridotomy. Results: The parameters as measured by Pentacam were mean CACD increased from 1.99 ± 0.21 to 2.03 ± 0.23 mm after LPI among PACS group with P = 0.01. There was no statistically significant increase in CACD among PAC and PACG groups. The change in the ACA was not statistically significant among all three groups. However, the average ACV increased from 77.50 ± 18.46 to 94.22 ± 16.62 mm3 in PACS, 82.09 ± 25 to 100.27 ± 25.76 mm3 in PAC, and 87.13 ± 19.32 to 101.62 ± 18.84 mm3 in PACG groups, respectively. Conclusion: Changes in anterior chamber parameter pre and post laser can be quantified adequately using pentacam.